2006
DOI: 10.1152/ajprenal.00521.2005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of basic functions in renal (patho)physiology

Abstract: Multiphoton fluorescence microscopy offers the advantages of deep optical sectioning of living tissue with minimal phototoxicity and high optical resolution. More importantly, dynamic processes and multiple functions of an intact organ can be visualized in real time using noninvasive methods, and quantified. These studies aimed to extend existing methods of multiphoton fluorescence imaging to directly observe and quantify basic physiological parameters of the kidney including glomerular filtration rate (GFR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(207 citation statements)
references
References 31 publications
(53 reference statements)
5
199
1
Order By: Relevance
“…This material is preferentially retained in the renal blood circulation, but slow filtration and tubular passage can also be followed. 1,23 For two-photon imaging of cortical areas containing mostly PTs (Supplemental Figure Figure 3A shows the renal PT baseline intracellular calcium levels visualized by GCaMP2 fluorescence, in relatively large kidney cortex areas. Of note, despite the relatively homogeneous GCaMP2 expression in the PTs (Figure 1), different PTareas showed different GCaMP2 fluorescence.…”
Section: Gcamp2 Expression In Kidney Pt Cells: In Vitromentioning
confidence: 99%
“…This material is preferentially retained in the renal blood circulation, but slow filtration and tubular passage can also be followed. 1,23 For two-photon imaging of cortical areas containing mostly PTs (Supplemental Figure Figure 3A shows the renal PT baseline intracellular calcium levels visualized by GCaMP2 fluorescence, in relatively large kidney cortex areas. Of note, despite the relatively homogeneous GCaMP2 expression in the PTs (Figure 1), different PTareas showed different GCaMP2 fluorescence.…”
Section: Gcamp2 Expression In Kidney Pt Cells: In Vitromentioning
confidence: 99%
“…Multiphoton excitation imaging was employed to quantitatively reveal microvascular function (Dunn et al, 2003;Molitoris & Sandoval, 2005) as well as glomerular filtration and permeability within kidney with living animals (Kang et al, 2006;Sipos et al, 2007). In a further study, they showed how this nonlinear optical imaging can be used to observe and quantify drug delivery in an intact, living and functioning kidney.…”
Section: In Vivo Drug Screening and Administration In Skin And Kidneymentioning
confidence: 99%
“…Indirectly, these studies also addressed the currently highly debated issue of the glomerular filtration of albumin. [14][15][16][17][18][19] To compare the glomerular processing of these two proteins, we employed intravital multiphoton fluorescence microscopy, which has been used by our laboratory 15,20,21 and the laboratories of others, [16][17][18][19] to directly and quantitatively visualize the glomerular permeability of macromolecules.…”
mentioning
confidence: 99%